1983
DOI: 10.3758/bf03199801
|View full text |Cite
|
Sign up to set email alerts
|

Consummatory response latency and the stimulus-reinforcer relation in autoshaping

Abstract: Autoshaping procedures with pigeons were used to assess the susceptibility of unconditioned response (UR) activity to Pavlovian relations between stimulus and reinforcer events. Foodpeck latency (a measure of UR activity) was investigated as a function of the interval between stimulus (keylight) and reinforcer (grain) presentations, and of the stimulus-reinforcer contingency, that is, the conditional probabilities of reinforcer delivery in the presence and absence of the stimulus. Four experiments indicated th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

1996
1996
2014
2014

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 42 publications
(47 reference statements)
0
4
0
Order By: Relevance
“…Because one can assume that it takes the bird some time to switch from pecking at the center key to pecking at the food in the hopper, the 1-s reinforcer did not actually represent access to food for one full second as scheduled. (For an experiment investigating food-peck latencies with 1-s hopper durations, see Brown, Coleman, & Elefant, 1983.) However, regardless of the amount of food that could be consumed when the 1-s alternative was chosen, the stimulus changes associated with reinforcement presentation were identical for the 1-s and the 6-s alternatives.…”
Section: Discussionmentioning
confidence: 99%
“…Because one can assume that it takes the bird some time to switch from pecking at the center key to pecking at the food in the hopper, the 1-s reinforcer did not actually represent access to food for one full second as scheduled. (For an experiment investigating food-peck latencies with 1-s hopper durations, see Brown, Coleman, & Elefant, 1983.) However, regardless of the amount of food that could be consumed when the 1-s alternative was chosen, the stimulus changes associated with reinforcement presentation were identical for the 1-s and the 6-s alternatives.…”
Section: Discussionmentioning
confidence: 99%
“…Note that B. Brown et al (1983) reported that UR potentiation did not, in fact, occur with pigeons and autoshaping. But they assessed changes in the UR in terms of latency to approach food, which, in contrast to the gape measure in our study, is not an obvious measure of topography.…”
Section: Response Topographymentioning
confidence: 98%
“…Second, differential peck rates may have reflected the pigeons' tendency to remain close to the right key because of prior reinforcement (cf. B. Brown, Coleman, & Elefant, 1983), thus decreasing performance on the left key.…”
Section: Response Rates and Latenciesmentioning
confidence: 99%
“…The target article provides a new and, perhaps, more general language for discussing issues that have been treated by various theories of operant-Pavlovian interactions (Davis & Hurwitz 1977;Locurto 1981;Rescorla & Solomon 1967;Williams 1981). These issues include the influence of feedback on the form of the Pavlovian conditioned responses (Konorski & Miller 1937;) and the modulation of operant (Rescorla & Solomon 1967) and unconditioned responses (UR's) (Brown et al 1983;Kimmel 1966) by Pavlovian conditioned stimuli (CS's). The emphasis in this article is on how the Pavlovian component contributes to the adaptiveness of behavior (cf.…”
Section: Introductionmentioning
confidence: 99%